DETERMINATION OF RESIDUES AND DISSIPATION KINETICS OF THIDIAZURON AND ITS METABOLITE IN DIFFERENT TROPICAL SOILS: Life Science - Environmental Sciences - PARVATAMMA, BOTSA; NAGESWARA RAO, TENTU (International Journal of Life Science and Pharma Research, 2017)
Thidiazuron play an important role in the production of crops, but their residues may cause numerous human/environmental problems. A study was conducted to evaluate the residues and dissipation kinetics of thidiazuron 50% WP in four different soils. The applied dosages are T0 – Untreated Control, T1 – thidiazuron 50% WP at 1 mg/kg of water and T2 – thidiazuron 50% WP at 2 mg/kg. Representative soil samples were collected on 0, 1, 3, 5, 10 and 20 days after spraying the formulation for the determination of residues of thidiazuron and its metabolite 1,2,3-Thiadiazol-5-ylurea by using a validated HPLC-PDA method. The method was used for the excellent separation of thidiazuron and its metabolite 1,2,3- Thiadiazol-5-ylurea in two different type soils is very short (around 15 min for a chromatographic run). he mean percent recovery of thidiazuron in Sandy loam, Loamy sand, Sandy clay and Clay soils was 85 ± 1.19; 87 ± 1.56; 89 ± 1.41 and 86 ± 1.78 at 0.03 mg/kg fortification level, 92 ± 2.15; 94 ± 2.56; 90 ± 2.69 and 95 ± 1.89 at 0.3 mg/kg fortification level. The mean percent recovery of metabolite 1, 2, 3-Thiadiazol-5-ylurea in Sandy loam, Loamy sand, Sandy clay and Clay soils was 89 ± 1.36; 86 ± 1.11; 87 ± 1.32 and 88 ± 1.77 at 0.03 mg/kg fortification level, 90 ± 2.41; 93 ± 2.82; 90 ± 2.71 and 92 ± 2.32 at 0.3 mg/kg fortification level. The LOQ was 0.03 mg/kg for thidiazuron and its metabolite 1, 2,3-Thiadiazol-5-ylurea. The half-life of thidiazuron was 4.73 and 4.90 days for T1 and T2 recommended doses in sandy loam, 4.61 (T1) and 4.84 (T2) days in loamy sand, 4.66 (T1) and 4.79 (T2) days in sandy clay and 4.71 (T1) and 4.78 (T2) days in clay soils respectively. Dissipation of thidiazuron in different tropical soils followed first order kinetics and this review describes a fast, simple sensitive analytical HPLC method.